SCIENTIFIC-METHODICAL BASIS OF INDUSTRIAL GEOGRAPHY OF UZBEKISTAN (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
The article describes the main features of the development of industrial food and the scientific directions of a number of scientists who conducted research in the field of industrial geography in Uzbekistan.